Intertwining social, affective, and digital dynamics: a masspersonal communication model to analyze home language maintenance - Chen, Jun-Yi; Liu, Ting-Ting (Frontiers in Psychology, 2025)
In multilingual families, sustaining home languages is increasingly challenged by digitalization and evolving communication patterns. This study proposes a new analytical model to analyze how home language development and maintenance are shaped by three overlapping communication contexts: interpersonal, mass, and masspersonal communication. Grounded in the masspersonal communication model (MPCM) proposed by O’Sullivan and Carr, the model highlights how emotional attachment, interactive routines, and cognitive perceptions operate across these contexts. Interpersonal communication fosters intimacy and habitual language use; mass communication amplifies access to linguistic resources and influences parental ideologies through media exposure; and masspersonal communication, blending public and private dimensions, enables performative, collaborative, and feedback-driven practices that strengthen language identity and emotional ties. Practical recommendations for policy, education, and family language practices are outlined, emphasizing integrative approaches to leverage these intersecting forces. This study addresses a key theoretical gap by offering a model that captures how digitally mediated environments reshape language practices at home. Future research is encouraged to empirically validate the model and to trace affective and cognitive dynamics in home language socialization. By revealing the complex interplay between digital technologies, social interactions, and linguistic identities, this study advances conceptual understanding of home language maintenance in an interconnected, multilingual world.